Thailand in the Cold War - Phillips, Matthew (Historian), author.
1 online resource (xiv, 217 pages)
Keywords: "Thailand's position during the Cold War was ambiguous: the country's political leadership was very keen to maintain the country's independence on the world stage, yet at the same time was anxious to establish the country's credentials as staunchly anti-communist. However, as this book argues, Thailand, though never formally a client state of the United States, was very closely embedded in the Western camp through the commitment of Thailand's cosmopolitan urban communities to developing a modern, consumerist lifestyle. Considering popular culture, including film, literature, fashion, tourism and attitudes towards Buddhism, the book shows how an ideology of consumerism and integration into a "free world" culture centred in the United States gradually took hold and became firmly established, and how this popular culture and ideology was fundamental in determining Thailand's international political alignment"--